2021
DOI: 10.1111/1467-9477.12195
|View full text |Cite
|
Sign up to set email alerts
|

Timing in Opposition Party Support under Minority Government

Abstract: Opposition parties under minority governments find themselves in a fundamental dilemma. They are competing with other parties, including the government, for electoral support while also having a common responsibility to make stable government work. This dilemma is especially pronounced for opposition parties signing support agreements with the government. While not formally in a coalition, they nonetheless publicly commit to supporting a government. They may thus be concerned about losing distinctiveness and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Besides, common control variables are included to avoid biased effects. To account for pressure from outside parliament, the analysis controls for the electorate saliency (measured for each committee/policy area using the importance ratings from the National SOM Survey cumulative data set) (University of Gothenburg, SOM Institute 2019) election years (Döring and Manow 2019), since the electoral cycle influences a support party's endorsement for the government (Müller and König 2021) as well as economic pressure. Arguing that despite being partly responsible for government stability, non-cabinet parties engage in party profiling, the electorate's opinion should play a major role when choosing strategies.…”
Section: Methods and Datamentioning
confidence: 99%
“…Besides, common control variables are included to avoid biased effects. To account for pressure from outside parliament, the analysis controls for the electorate saliency (measured for each committee/policy area using the importance ratings from the National SOM Survey cumulative data set) (University of Gothenburg, SOM Institute 2019) election years (Döring and Manow 2019), since the electoral cycle influences a support party's endorsement for the government (Müller and König 2021) as well as economic pressure. Arguing that despite being partly responsible for government stability, non-cabinet parties engage in party profiling, the electorate's opinion should play a major role when choosing strategies.…”
Section: Methods and Datamentioning
confidence: 99%
“…Support parties can claim credit for successful policies, but avoid blame when a policy fails. Recent studies have explored this argument in more detail and found that external support parties tend to successfully attain their policy goals (Anghel & Thürk, 2021), that they tend to downplay their support of the government during election campaigns (Müller and König, 2021) and on issues that are salient to them (Müller, 2022). Generally, they are less constrained in what issues they emphasize, which might explain why their electoral performance is similar to that of “true” opposition parties (Thesen, 2016).…”
Section: Pseudo-opposition and Quasi-majoritiesmentioning
confidence: 99%
“…In contrast, Tuttnauer and Wegmann (2022) argued that opposition parties should take a conflictual stance and differentiate themselves ideologically. The latter finding suggests that support parties, much like coalition members, have strong electoral incentives to signal distinctiveness especially when elections are approaching (Müller & König, 2021). Failure to do so will likely cause voters to lump the support parties in with the government and prevent them from representing a credible alternative.…”
Section: Hypothesesmentioning
confidence: 99%
“…As Müller (2022) points out, support parties have strong incentives for highlighting their unique party profile and distinguish themselves from the governing parties (see also Müller & König, 2021; Tuttnauer & Wegmann, 2022). It is thus quite likely that support parties have no ambitions of joining the cabinet but prefer their access to policy influence without being associated with and held responsible for government actions (Strøm, 1990).…”
Section: Accountability Under Minority Governmentsmentioning
confidence: 99%